2016
DOI: 10.1016/j.pharmthera.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

αB-crystallin: Portrait of a malignant chaperone as a cancer therapeutic target

Abstract: αB-crystallin is a widely expressed member of the small heat shock protein family that protects cells from stress by its dual function as a molecular chaperone to preserve proteostasis and as a cell death antagonist that negatively regulates components of the conserved apoptotic cell death machinery. Deregulated expression of αB-crystallin occurs in a broad array of solid tumors and has been linked to tumor progression and poor clinical outcomes. This review will focus on new insights into the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 129 publications
(264 reference statements)
2
41
0
Order By: Relevance
“…6). This observation is consistent with the antiapoptotic function of CryAB previously reported by others (13,15,22). A recent study by Volkmann et al (34) further showed that overexpression of CryAB protected against cisplatin-induced apoptosis in human ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…6). This observation is consistent with the antiapoptotic function of CryAB previously reported by others (13,15,22). A recent study by Volkmann et al (34) further showed that overexpression of CryAB protected against cisplatin-induced apoptosis in human ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…This nuclear PI4,5P 2 pathway for controlling p53 stability has significant implications for cancer. Although PIPKIα, mutant p53, and sHSPs have independently been implicated in tumor progression 12,15,58,60 , our results indicate that these proteins form a carefully orchestrated molecular complex that may contribute to these effects. Intriguingly, p53 mutation was recently reported to lead to an increase in phosphoinositides 63 that are favored substrates for PIPKIα 64 .…”
Section: Discussionmentioning
confidence: 76%
“…Not only mutant p53 but also wild-type p53 have an intrinsic proclivity to form homo-and hetero-aggregates and the DBD is responsible for self aggregation 42,56,57 . sHSPs do not have ATPase activity, but under stress conditions sHSPs form large oligomeric complexes that bind to unfolded clients 58 . This chaperone-like activity of sHSPs protects client proteins from aggregation and degradation 47,[58][59][60] and may also support specific functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of cancer, there does not appear to be a clear consensus as to whether CRYAB supports or suppresses tumorigenesis [30]. Many studies conclude a pro-tumorigenic effect of CRYAB and a positive correlation between its expression and tumor aggression [31], whereas others report a tumor-suppressive activity and/or decreased expression in more aggressive tumors [32,33]. Our results suggest that cancer type is one factor determining whether CRYAB exerts an inhibitory or supportive role in a tumor, and that renal carcinomas in particular may be susceptible to CRYAB-modulating therapies.…”
Section: Pan-cancer Featuresmentioning
confidence: 99%